Progesterone, progesterone/estradiol and ART outcomes in day-5 transfer cycles. (2nd January 2018) - Arora, Ritika; Chan, Crystal; Ye, Xiang Y.; Greenblatt, Ellen M.
Abstract: The objective of this study was to assess the effects of elevated luteal-phase progesterone levels (PE) and high progesterone/estradiol ratio ('P/E2' ratio) on IVF outcomes, exclusively in GnRH-antagonist cycles with day-5 embryo transfer. PE was not found to have a significant effect on implantation or clinical pregnancy rate (CPR) (OR 0.56, 95% CI 0.25–1.25, p  = .16). Elevated 'P/E2' ratio (≥0.55) on trigger day was associated with a poorer response to stimulation and lower clinical pregnancy rates (OR 0.58, 95% CI 0.34–1.00, p  = .05). Patients with PE and low 'P/E2' ratio yielded significantly more oocytes than patients with PE and high 'P/E2' ratio. The mean implantation rate per patient decreased by 60% in the group with PE and high 'P/E2' ratio in comparison to the group with PE and low 'P/E2' ratio (17.9%±36.6 vs. 45.5%±47.2, p  = .06), although no statistical significance was observed. The detrimental effect of PE may be mitigated by culturing embryos to day-5 before embryo transfer. Combined assessment of serum progesterone and 'P/E2' ratio may predict pregnancy outcome better than progesterone levels alone.